2009
DOI: 10.1590/s0102-05362009000300015
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of tomato genotypes to the silverleaf whitefly mediated by acylsugars

Abstract: Acylsugars in the leaflets of the wild accession LA-716 (Lycopersicon pennellii) gives resistance to Bemisia spp., which causes expressive losses to the tomato crop. The goal of this work was to evaluate the resistance to the silverleaf whitefly (Bemisia tabaci biotype B) of previously selected genotypes, based on the level of acylsugars in the leaflets. F 2 BC 1 plants {F 2 [Lycopersicon esculentum TOM 584 x (L. esculentum TOM 584 x L. pennellii LA-716)]} were selected for extreme contents of acylsugars: BPX-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 15 publications
3
24
0
6
Order By: Relevance
“…Volatile organic compounds may reduce whitefly impact on tomato (Guo et al 2013), mainly via repellence but also via potential toxic effects (Bleeker et al 2011). Glandular trichomes on leaf surfaces, particularly type IV and type VI (Firdaus et al 2013), have been shown to physically ensnare whitefly (Toscano et al 2002) and exude deterrent or toxic chemicals such as acyl sugars (de Resende et al 2009). Other physical methods are also important in determining host susceptibility, such as cuticle and epidermis thickness (Toscano et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Volatile organic compounds may reduce whitefly impact on tomato (Guo et al 2013), mainly via repellence but also via potential toxic effects (Bleeker et al 2011). Glandular trichomes on leaf surfaces, particularly type IV and type VI (Firdaus et al 2013), have been shown to physically ensnare whitefly (Toscano et al 2002) and exude deterrent or toxic chemicals such as acyl sugars (de Resende et al 2009). Other physical methods are also important in determining host susceptibility, such as cuticle and epidermis thickness (Toscano et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the ability of wild tomato species to resist B. tabaci, e.g. Firdaus et al (2012), Rodríguez-López et al (2011) (which both included accessions of the wild tomato species considered here), Firdaus et al (2013) andde Resende et al (2009). Work to elucidate the source of whitefly resistance in wild tomato species has also been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Linhagens com resistência múltipla a doenças são relativamente frequentes em bancos de germoplasma de programas de melhoramento, o mesmo não acontece com linhagens resistentes a pragas. Recentemente, tornaram-se disponíveis algumas linhagens de tomateiro que aliam boas características comerciais com altos teores foliares de acilaçúcares (AA) (Maciel, 2008), aleloquímicos associados à resistência a uma gama de pragas da cultura (Pereira et al, 2008;Resende et al, 2006Resende et al, , 2008Resende et al, , 2009Silva et al, 2008).…”
Section: Introductionunclassified
“…Gonçalves et al (2007) indicaram que altos teores de AA se devem à ação de um alelo recessivo, com dominância incompleta no sentido de baixos teores. Plantas com altos teores de AA foram resistentes à mosca branca Bemisia argentifolii Bellows & Perring (Homoptera: Aleyrodidae) (Liledl et al, 1995;Maciel, 2008;Resende et al, 2009) e aos ácaros Tetranychus spp (Saeidi et al, 2007;Maciel, 2008;Pereira et al, 2008;Resende et al, 2008) e tiveram confirmada sua resistência à traça Tuta absoluta (Meyrick, 1917) (Lepidóptera: Gelechiidae) (Resende et al, 2006) em gerações segregantes. Tal fato se reveste de especial importância, pois embora a resistência a pragas em tomateiro mediada por AA seja bem documentada (Goffreda et al, 1989;Juvik et al, 1994;Liedl et al, 1995;Gonçalves et al, 2007;Resende et al, 2006Resende et al, , 2008Saeidi et al, 2007;Maciel, 2008), ainda não estão disponíveis, no mercado, tomateiros comerciais com níveis satisfatórios de resistência.…”
Section: Introductionunclassified
“…With increased demand for tomato based products by the consumer, as well as increased demand for high quality products with low agrochemical indexes, alternative methods of control have been used in an attempt to reduce the use of chemical products; this includes the use of resistant genotypes, which have shown promise in the fight against arthropod pests (Resende et al, 2009;Silva et al, 2009;Oliveira et al, 2012;Dias et al, 2013;Neiva et al, 2013;Lucini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%